A nutritional profile of patients with tuberculosis at Standerton Tuberculosis Specialised Hospital, Mpumalanga, South Africa - Janke Wessels; Mariette Nel; Corinna M. Walsh (AOSIS, 2021)
Background: Tuberculosis (TB) is strongly influenced by nutritional status, with nutrition interventions being likely to have an impact on the prevalence of disease, response to drugs and quality of life. Aim: The aim of this research study was to determine the nutritional profile of patients with TB and TB and human immunodeficiency virus (HIV) co-infection. Setting: The study was conducted at Standerton TB Specialised Hospital, Mpumalanga. Methods: A cross-sectional study was undertaken. A structured interview was conducted by the researcher with each patient. The Malnutrition Universal Screening Tool (MUST) was used to determine the risk of malnutrition. Weight, height, mid-upper arm circumference (MUAC) and triceps skinfold were measured using standard techniques. Biochemical parameters that were part of the routine hospital procedure were noted. Results: More than two-thirds of the participants (68%) were found to be HIV positive. Food-related side effects included loss of appetite (59%) and dry mouth (48%). According to the MUST, 70% had a high risk of malnutrition. The median body mass index (BMI) was in the underweight category at 18.3 kg/m². About half of the participants had low MUAC measurements (51%) and triceps skinfold measurements below the 15th percentile (49.9%), indicating malnutrition. Most participants had low albumin and haemoglobin levels (79% and 92%, respectively). Conclusions: Patients with both TB and TB and HIV co-infection had a compromised nutritional status and an increased risk for developing malnutrition. Interventions aimed at addressing malnutrition could make a meaningful contribution to improving the quality of life in these patients. Contribution: This research provides evidence on the nutritional profile of patients with tuberculosis at Standerton TB Specialised Hospital, it gives opportunity to extend this research project to confirm these findings in other TB burdened areas.